Courtroom perceptions of child sexual assault: the impact of an eyewitness - Golding, Jonathan M. (Criminal justice and behavior, 2015)
One hundred eighty-two undergraduates (96 women) read a summary of a child sexual assault (CSA) criminal trial involving a 6-year-old alleged victim. The trial summaries differed as to whether an eyewitness to the CSA other than the victim testified in court and the age of that eyewitness (6 or 36 years old). The results showed that the additional witness did not affect women?s pro-victim judgments, but significantly increased men?s pro-victim judgments. Furthermore, compared with women, men felt more anger toward the defendant when the additional witness testified. A follow-up experiment (43 women) included an additional witness who did not witness the CSA. The results of this follow-up showed that rather than the number of witnesses, it was the additional witness to the CSA that increased pro-victim judgments. The results are discussed in terms of how additional corroborating testimony in a CSA case affects men and women jurors.